MATHEMATICAL MODEL OF SPATIAL FLUCTUATIONS OF PASSENGER CASR IN THE USUAL FORMULATION - Pshinko, O. M.; Myamlin, S. V.; Prykhodko, V. I.; Shkabrov, O. A.; Ihnatov, H. S.; Donchenko, A. V.; Fiediushyn, Yu. M. (Science and Transport Progress, 2005)
In article the mathematical model for studying spatial fluctuations of carriages on which extensive theoretical researches on studying new models of carriages of manufacture car-building factory Kryukov are lead is offered. Researches further were carried in a working range of speeds 20…200 km/h on various sites of a way. Results of calculations have proved design decisions.